ANALYSIS OF THE APPLICATION OF ISAK 35 IN THE FINANCIAL STATEMENTS OF THE DOMPET DHUAFA FOUNDATION (Case Study of the Dompet Dhuafa Foundation) - Ratna Mutiara Andhani; Arni Karina; Kumba Digdowiseiso (SEAN Institute, 2023)
The aim of this research is to analyze the application of ISAK 35 to the financial reports of the Dompet Dhuafa Foundation for the 2020 financial year. The research method used is a qualitative descriptive method. This research data is data obtained directly by the research object consisting of financial reports for September, October, November 2020. It is hoped that this research can be a reference for other research related to ISAK 35 considering that the majority of research conducted previously discussed PSAK 45. And it can be used as input and consideration for the management of the wallet dhuafa foundation in implementing ISAK 35 for financial reporting. Based on the research results, it shows that the Dompet Dhuafa Foundation's financial reports have implemented PSAK 109, namely regarding Accounting for Zakat and Infaq or Alms, while ISAK 35 has not been fully implemented. Thus, the format, account names and recognition, measurement, presentation and disclosure in the financial reports of the Dompet Dhuafa Foundation are said to be not in accordance with ISAK 35.